Experimental evaluation of the fatigue life of hydraulic gate cast iron rollers. Issue 2 (9th February 2020) - Lashari, Abdul Nabi; Polyzois, Ioannis; Polyzois, Dimos
Abstract: Fixed‐wheel gates with wheels mounted on both sides that roll on roller path plates are used in both emergency intake gates and spillway gates in hydrogenerating stations. Environmental corrosion along with high wheel loads cause differences in the profile of the roller path surface. Combined with the relatively high torsional stiffness of the gate end girders, a condition of wheel load redistribution occurs where some wheels are relieved of load while others are loaded beyond their maximum design values. Failure of one wheel could jeopardize the overall operation of the gate. Furthermore, frequent operation of these gates result in changes in the stress profile in both wheels and roller paths that, potentially, could lead to failure. Currently, design guidelines for gate wheels and roller paths do not consider the fatigue life of these elements. Research‐based evidence is provided to support changes to these guidelines. Abstract : Fixed‐wheel gates with wheels mounted on both sides that roll on roller path plates are used in both emergency intake gates and spillway gates in hydro‐generating stations. Currently, design guidelines for gate wheels and roller paths do not consider the fatigue life of these elements. Research‐based evidence is provided to support changes to these guidelines.